Effects of pomegranate peel extract, green tea extract, and supercritical carbon dioxide on physicochemical and microbial quality of chicken meat - Jauhar, Safiullah (2020)
Companies and consumers are showing strong interest in natural antioxidants due to their safe, non-toxic, and natural attributes. Supercritical carbon dioxide (SC-CO2) has been adopted in food, pharmaceutical, and similar industries to improve microbial safety and food sterilization. The effect of the microbial and physicochemical properties of Pomegranate (Punica granatum L.) peel extract (PPE), green tea (Camellia sinensis) extract (GTE), and SC-CO2 on chicken meat is still unknown. Hence, this work aims to determine the microbial and physicochemical quality of chicken meat treated with PPE, GTE, PPE + GTE. Three levels of SC-CO2 (7.4 MPa, 11.4 MPa, and 15.4 MPa pressure at 31°C for 10 min) were applied, then a combination of the best conditions of phenolic content and SC-CO2 were evaluated. The extraction process of PPE and GTE was done using ultrasound-assisted extraction (UAE) and solid-liquid extraction (SLE). Both extracts resulted in high phenolic content, but the extracts produced using the UAE method showed higher antioxidant activity than SLE. The extracts were then applied on the chicken meat using 0.02% extracts based on a muscle-to-liquid ratio of 1:2 across four treatments: the control (meat + distilled water), (meat + PPE), (meat + GTE), and (meat + PPE + GTE). The PPE, GTE, and GTE + PPE notably inhibited the total plate count (log CFU/g) of the meat, reducing it to 5.89 ± 0.54 log CFU/g, 5.47 ± 0.32 log CFU/g, and 6.50 ± 0.31 log CFU/g, respectively, from 6.81 ± 0.68 log CFU/g in the control meat sample on the third day. The microstructure of all treatments was significantly different than the control sample. The colour of the meat was significantly improved with the application of the extracts, particularly the ‘b’ value with GTE showing a higher value than the other treatments. No significant (p > 0.05) changes were recorded for the cooking loss, water holding capacity, and sensory attributes of the meat; the springiness texture was remarkably improved with the application of the extracts. The meat quality and microbial reduction were also improved as a result, with GTE showing a better result than the other treatments. The best SC-CO2 condition (15.4 MPa) was combined with 0.02% GTE and applied to the meat and stored at 4°C for 0, 3, and 7 days. Both treatments i.e. SC-CO2 alone and in combination with GTE significantly improved (p < 0.05) microbial safety. The 15.4 MPa and 11.4 MPa SC-CO2 conditions sequentially inhibited microbe growth compared to the control on zero-day. The microbial inhibition of the combined treatment was significantly effective on the zero and seventh days of storage. Different levels of SC-CO2 alone did not affect peroxidation, cooking loss, or water holding capacity. The microstructure of all treatments was significantly different compared to the control. The combined treatment was remarkably effective for upgrading cooking yield, redness and yellowness, peroxidation, cohesiveness, gumminess, and resilience. Hence, high-pressure (15.4 MPa) of SC-CO2 is recommended more than the medium- and low-pressure SC-CO2 in combination with GTE to preserve chicken meat compared to its treatment alone.